PENGARUH BIMBINGAN KLASIKAL UNTUK MENURUNKAN PROKRASTINASI AKADEMIK SISWA SMA NEGERI 1 TAMBANG - Nurizah Nurizah; Elni Yaqub; Mahdum Mahdum (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstrack:Academic procrastination is a behavior carried out by someone by delaying doing the tasks given by the teacher. The purpose of this study was to determine the effect of classical guidance on reducing student academic procrastination at SSMA Negeri 1 Tambang. This type of research is a quasi-eksperiment design. This study uses a design in the form of one group pretest-posttest. The subjects of this study were 32 students of class XI IPS who had high academic procrastination bassed on the academic procrastination measurement scale with 6 meetings. The results of the study indicate that there is an influence of classical guidance to reduce academic procrastination of students at SMA Negeri 1 Tambang.Key Words: Academic Procrastination, Influence, Classical Guidance